Effect of diabetes mellitus on association between galectin-3 and H2FPEF score in patients with unexplained dyspnea and a preserved left ventricular ejection fraction - Dogdu, Orhan; Karasu, Mehdi; Karaca, Yuecel; Harman, Murat (Wiley, 2023)
ObjectivesThe aim of this study was to investigate the effect of diabetes mellitus (DM) on the association between Galectin-3 (Gal-3) and the H2FPEF score in patients with unexplained dyspnea and a preserved left ventricular ejection fraction (LVEF).MethodsA cross-sectional observational study was conducted on patients with unexplained dyspnea and a preserved LVEF in the Cardiology Department of Elazig Medical Park Hospital, Turkey. The patients were evaluated based on the presence of DM and the H2FPEF score. Gal-3 levels were compared between groups, and the effect of DM on Gal-3 was assessed. The level of statistical significance in all tests was set at p < .05.ResultsGal-3 and H2FPEF scores were higher in patients with DM (p < .001 and p = .027, respectively). Gal-3 and HbA1C values were elevated in patients with moderate to high H2FPEF scores (p < .01 and p = .036, respectively). DM and Hypertension were more prevalent in patients with moderate to high H2FPEF scores (p = 0.024, p < 0.001, respectively). A strong correlation was observed between Gal-3 and the H2FPEF score (r = 0.375, p < .001). Gal-3 could predict patients with a moderate to high H2FPEF score using a cut-off value of 14.7, with a sensitivity of 69% and specificity of 67% (AUC: 0.702).ConclusionsGal-3 serves as an independent predictor of the H2FPEF score in the presence of DM, and the diagnostic capability of Gal-3 for Heart Failure with preserved LVEF remains unaffected by DM.
Keywords: Heart-Failure; Natriuretic Peptide; Inhibition; Marker; Macrophages; Prognosis; Fibrosis